The Effect of Special Visual Exercises in the Development of Visual Tracking and the Accuracy of Spike in the Volleyball for Young Players - Bassem Hassan Ghazi (Journal of Global Pharma Technology, 2018)
The Aims of Research toPreparation of visual exercises, especially in the development of visual tracking and the accuracy of the spike of the volleyball young players.To identify the impact of exercise visual especially in the development of visual tracking and the accuracy of the spike of the volleyball of young players.The Hypothesis wasSpecial visual exercises have a positive effect on the development of visual tracking and the accuracy of the volleyball spiking of young players.As for the research method, the researchers chose the experimental approach as the appropriate method to solve the research problem by designing the experimental and control groups with the tribal and remote tests as it fits the nature of the research problem.The sample of the research was chosen from the research community represented by the young players in the volleyball of the middle region (3 clubs) in Iraq at the age of 17-19 years and the number of (36) player has been selected two clubs, including the number of (20) player after the expulsion of the player prepared randomly by lot to represent the two groups Experimental and control of the sample of the search and the reality of (10) player for each group.The Researchers ConcludedAn evolution in visual tracking and accuracy of the volleyball team's spikein volleyball skill.There is a preference for the experimental group in the tests of the dimension of visual tracking and the accuracy of spiking in the volleyball.The various special exercises developed by the researchers contributed to the development of visual tracking and the accuracy of the spiking skill.The recommendations wereThe need to use special visual exercises to develop the visual tracking of players, especially young people.The need to use special visual exercises to increase the accuracy of the skill of spiking.The need to use special visual exercises to increase the excitement and excitement of young people and increase their motivation for training.Keywords: Visual exercises, Accuracy, Spike and volleyball.